Home-schooling and caring for children during the COVID-19 lockdown in the UK: emotional states, systems of support and coping strategies in working mothers - Kallitsoglou, Angeliki; Topalli, Pamela-Zoe (Frontiers in Sociology, 2024)
We examined the experience of home-schooling and/or caring for children in working mothers during the first national COVID-19 lockdown in the UK, their emotional responses to the experience, and the ways they coped with the challenges that came with it. Eligible working mothers (n = 47; Mage = 39.6) participated in an anonymous online survey of open-ended questions. Thematic analysis of maternal responses showed that home-schooling and/or caring for children was often perceived as a challenging experience. However, a few mothers appreciated the opportunity for greater involvement in their child’s life and learning. The analysis revealed a wide range of mental states associated with the experience of home-schooling/caring. The most reported emotions were stress about managing competing demands, guilt of not meeting the child’s needs, and worry over child well-being and academic learning and increasing demands at work. Maternal experiences and emotional states were relevant to their perceptions of the amount and type of support they had available and the coping strategies they used to adapt to the practical and emotional challenges of home-schooling/childcare. Common strategies included adopting a positive outlook, implementing flexible family structures, increased family connectedness, and negotiating alternative partnership models. The findings have implications for post-pandemic recovery measures and for maternal well-being in the face of adversity.